Prinsip Etika Lingkungan Hidup dalam Novel Serdadu Pantai Karya Laode Insan - Ilham Wahyudi; Noni Andriyani (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to find out the ethical principles of the environment in the novel Serdadu Pantai Karya Laode Insan, with a total of 36 data collected. This study uses a descriptive approach. In researching literary works, formal qualitative research data is obtained from novel texts in the form of words, sentences, and discourse. The results of this study found 7 principles of environmental ethics, namely, the principle of compassion and respect for nature, the principle of living simply and in harmony with nature, the principle of democracy, the principle of responsibility, the principle of respect for nature, the principle of cosmic solidarity, and the principle of not harming. where 2 of the principles were not found, namely the principle of justice and the principle of moral integrity. The principle of living in harmony and simplicity with nature is most commonly found in the beach soldier novel by Laode Insan.